ESPEN expert group recommendations for action against cancer-related malnutrition. Issue 5 (October 2017) - Arends, J.; Baracos, V.; Bertz, H.; Bozzetti, F.; Calder, P.C.; Deutz, N.E.P.; Erickson, N.; Laviano, A.; Lisanti, M.P.; Lobo, D.N.; McMillan, D.C.; Muscaritoli, M.; et al.
Summary: Patients with cancer are at particularly high risk for malnutrition because both the disease and its treatments threaten their nutritional status. Yet cancer-related nutritional risk is sometimes overlooked or under-treated by clinicians, patients, and their families. The European Society for Clinical Nutrition and Metabolism (ESPEN) recently published evidence-based guidelines for nutritional care in patients with cancer. In further support of these guidelines, an ESPEN oncology expert group met for a Cancer and Nutrition Workshop in Berlin on October 24 and 25, 2016. The group examined the causes and consequences of cancer-related malnutrition, reviewed treatment approaches currently available, and built the rationale and impetus for clinicians involved with care of patients with cancer to take actions that facilitate nutrition support in practice. The content of this position paper is based on presentations and discussions at the Berlin meeting. The expert group emphasized 3 key steps to update nutritional care for people with cancer: (1) screen all patients with cancer for nutritional risk early in the course of their care, regardless of body mass index and weight history; (2) expand nutrition-related assessment practices to include measures of anorexia, body composition, inflammatory biomarkers, resting energy expenditure, and physical function; (3) use multimodal nutritional interventions with individualized plans, including care focused on increasing nutritional intake, lessening inflammation and hypermetabolic stress, and increasing physical activity.